2020
DOI: 10.3389/fmicb.2020.01583
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Bioinformatic Analyses of Nidovirales Including Human SARS-CoV-2, SARS-CoV, MERS-CoV Viruses Suggest Important Roles of Non-canonical Nucleic Acid Structures in Their Lifecycles

Abstract: Non-canonical nucleic acid structures play important roles in the regulation of molecular processes. Considering the importance of the ongoing coronavirus crisis, we decided to evaluate genomes of all coronaviruses sequenced to date (stated more broadly, the order Nidovirales) to determine if they contain non-canonical nucleic acid structures. We discovered much evidence of putative G-quadruplex sites and even much more of inverted repeats (IRs) loci, which in fact are ubiquitous along the whole genomic sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 113 publications
7
64
0
Order By: Relevance
“…Our results showed an enrichment for RBPs such as SRSFs, PCBPs, ELAVs, and HNRNPs being most likely to get sponged on the viral genome ( Figure 4 B). Our observation that specific RBPs such as SRSF7, HNRNPA1, and TRA2A with a well-known role in splicing exhibiting binding sites on SARS-CoV-2 RNA is in agreement with a recently published study [ 85 ]. We found that most of these RBPs were abundantly expressed in gonadal tissues; adrenal tissues; the pancreas; and immune cells, including B cells, CD4+ T cells, and NK cells ( Figure 4 B).…”
Section: Resultssupporting
confidence: 93%
“…Our results showed an enrichment for RBPs such as SRSFs, PCBPs, ELAVs, and HNRNPs being most likely to get sponged on the viral genome ( Figure 4 B). Our observation that specific RBPs such as SRSF7, HNRNPA1, and TRA2A with a well-known role in splicing exhibiting binding sites on SARS-CoV-2 RNA is in agreement with a recently published study [ 85 ]. We found that most of these RBPs were abundantly expressed in gonadal tissues; adrenal tissues; the pancreas; and immune cells, including B cells, CD4+ T cells, and NK cells ( Figure 4 B).…”
Section: Resultssupporting
confidence: 93%
“…4B ). Specifically, our observation of RBPs well known for their role in splicing such as SRSF7, HNRNPA1 and TRA2A was in accordance with a recently published study that predicted binding sites of these RBPs on SARS-CoV-2 RNA [ 65 ]. In summary, these findings suggest that SARS-CoV-2 could sponge human RBPs on its genome resulting in altered post-transcriptional gene regulatory network in the host cells.…”
Section: Resultssupporting
confidence: 91%
“…4B). Our observation that specific RBPs such as SRSF7, HNRNPA1 and TRA2A with well-known role in splicing exhibited binding sites on SARS-CoV-2 RNA, is in agreement with a recently published study [85]. We found that most of these RBPs were abundantly expressed in gonadal tissues, adrenal tissues, pancreas, and immune cells including B cells, CD4+ T cells and NK cells (Fig.…”
Section: Motif Enrichment Analysis Reveals Potential Human Rbps Titrasupporting
confidence: 92%
“…The propensity of the ORF8 region to suffer deletions has raised the hypothesis that RNA secondary structures could play a role in their formation ( Consortium, 2004 ). Several hairpin structures have been already detected in SARS-CoV-2 ( Andrews et al, 2020 ; Bartas et al, 2020 ; Lan et al, 2020 ; Rangan et al, 2020 ; Simmonds, 2020 ).…”
Section: Introductionmentioning
confidence: 99%